2011
DOI: 10.2310/8000.2011.100220
|View full text |Cite
|
Sign up to set email alerts
|

Using cervical spine clearance guidelines in a pediatric population: a survey of physician practices and opinions

Abstract: Background: Unlike in adults, there are currently no standardized, validated guidelines to aid practitioners in clearing the pediatric cervical spine (C-spine). Many pediatric centres in Canada have locally produced, adult-modified guidelines, but theextent towhichtheseorotherguidelinesareusedisunknown. Objective: The purpose of this study was to determine if Canadian physicians are using either locally produced or adult C-spine guidelines to clear the C-spines of patients , 16 years of age. The study also cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…A survey of 240 pediatric emergency physicians and trauma team leaders in Canada found that those trained in emergency medicine and critical care are more likely than those trained in family medicine or pediatrics to use a guideline. 33 A survey conducted before the publication of the NEXUS and CCR criteria found that physicians trained in either pediatrics or pediatric emergency medicine were twice as likely to clear a patient with a reassuring examination without using radiographs when compared with emergency medicine-trained physicians. 34 Overall, pediatric practice of clearing cervical spine injuries is highly variable among providers and institutions.…”
Section: Pediatric Cervical Spine Clearance Practicementioning
confidence: 99%
“…A survey of 240 pediatric emergency physicians and trauma team leaders in Canada found that those trained in emergency medicine and critical care are more likely than those trained in family medicine or pediatrics to use a guideline. 33 A survey conducted before the publication of the NEXUS and CCR criteria found that physicians trained in either pediatrics or pediatric emergency medicine were twice as likely to clear a patient with a reassuring examination without using radiographs when compared with emergency medicine-trained physicians. 34 Overall, pediatric practice of clearing cervical spine injuries is highly variable among providers and institutions.…”
Section: Pediatric Cervical Spine Clearance Practicementioning
confidence: 99%
“…7 Thus, clinicians remain uncertain about which clinical screening criteria, if any, to use when evaluating children for potential cervical spine injury after blunt trauma. 8,9 For the symptomatic patient, it is generally agreed that radiographic imaging is a necessary adjunct, but there are no consistent recommendations on indications or modality. Adult…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Although childhood trauma is a major cause of mortality and morbidity, the incidence of spinal trauma is significantly lower in children than in adults [1]. Pediatric spinal trauma (PST) comprises 1–10% of all spinal injuries [2].…”
Section: Introductionmentioning
confidence: 99%